The role of cognitive motivation and self-regulation in coping with occupational demands - Hoff, Inga; Farkas, Aniko; Melicherova, Ursula; Köllner, Volker; Hoyer, Jürgen; Strobel, Alexander; Strobel, Anja (Frontiers in Psychology, 2024)
Cognitive motivation (COM) in conjunction with self-regulation (SR) was demonstrated to be positively linked to mental health in educational and clinical contexts. We introduce COM and SR in the occupational context and hypothesize these traits—based on their conceptual link to hardiness - to counteract health-risking stressors. Data from two large cross-sectional studies in Germany comprise a sample of 1,022 psychosomatic rehabilitation in-patients and a healthy sample of 298 employees of various occupations. Using bootstrapping in correlation analyses, we found in both samples COM and SR to be especially associated with an active, meaningful, and persistent coping style (0.31 ≤ r ≤ 0.57). Analyses via structural equation modeling found COM cross-sectionally predicting occupational coping via SR in both samples. We discuss COM and SR as personal resources with respect to Conservation of Resources Theory and provide ideas for promoting these variables in patients and employees.